The law of contract - O'Sullivan, Janet (Core text series, 2014)
"The Law of Contract provides an accessible overview of the fundamentals of contract law and its underlying rationales. It also introduces and explores the main academic debates within the subject, encouraging students to decide for themselves whether the rules that contract law adopts are justifiable and, if not, how they should be altered. To help students to develop the skills necessary to apply the principles of contract law to new situations, The Law of Contract breaks down legal problems into different and manageable steps. This book covers all of the core areas studied on an undergraduate course and incorporates chapter summaries and self-test questions to reinforce students' learning and aid revision, as well as further reading sections to provide a platform for further study. Online Resource Center Updates Web links"--